2011
DOI: 10.1083/jcb.201106146
|View full text |Cite
|
Sign up to set email alerts
|

Two single-headed myosin V motors bound to a tetrameric adapter protein form a processive complex

Abstract: The yeast class V myosin Myo4p moves processively in vivo in a cargo-dependent manner following formation of a double-headed complex with the adapter protein She3p and the mRNA-binding protein She2p.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
49
4

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(55 citation statements)
references
References 55 publications
2
49
4
Order By: Relevance
“…Contrary to the proposal (13,16,26) that Myo4p•She3p form a 1:1 heterodimer, our data show that Myo4p and She3p associate instead in a 1:2 heterotrimer. Specifically, we found that a pseudocoiled-coil region of two She3p molecules forms an extensive binding platform for the C-terminal domain (CTD) of a single Myo4p molecule.…”
Section: Significancecontrasting
confidence: 55%
See 4 more Smart Citations
“…Contrary to the proposal (13,16,26) that Myo4p•She3p form a 1:1 heterodimer, our data show that Myo4p and She3p associate instead in a 1:2 heterotrimer. Specifically, we found that a pseudocoiled-coil region of two She3p molecules forms an extensive binding platform for the C-terminal domain (CTD) of a single Myo4p molecule.…”
Section: Significancecontrasting
confidence: 55%
“…1B and 5A). Collectively, these data overturn the view that Myo4p and She3p associate with each other as a 1:1 heterodimer and are doing so via a dedicated helical region in each molecule (13,23,26). They also contradict the idea that Myo4p and She3p molecules can associate with each other to form a complex of two Myo4p molecules and an unspecified number of She3p molecules (25).…”
Section: Discussioncontrasting
confidence: 43%
See 3 more Smart Citations